The effect of asset growth and company size on company value with profitability as a moderating variable - M Amin; Ikhwan Wadi (Institute of Accounting Research and Novation (IARN), 2022)
This study aims to empirically examine the effect of Asset Growth and Company Size on firm value with profitability as a moderating variable case study on metal companies and the like listed on the Indonesia Stock Exchange over five periods from 2012-2016. This research is a sociative with a form of causal relations. The population in this study were all metal companies and the like listed on the Indonesia Stock Exchange from 2012 to 2016 with the total 16 companies. Sampling in this study used a purposive sampling method. Based on predetermined Criteria, 12 companies were obtained as research samples so that the amount of data processed was 60. Based on the results of data analysis, profitability is not able to moderate the effect of asset growth on the value of the company in metal and similar companies listed on the Indonesia Stock Exchange in 2012-2016. This is indicated by the regression coefficient value of the variable between the growth of assets and profitability (X1.X3) of -0.009 with the value of t <t table (-0.351 <2.00247) with a significance level of 0.727> 0.05. Profitability is not able to moderate the effect of company size on the value of the company in metal companies listed on the Indonesia Stock Exchange in 2012-2016. This is indicated by the variable regression coefficient of interaction between firm size and profitability (X2.X3) of -0.068 with t count <t table (-1.797 <2.00247) with a significance level of 0.078> 0.05